1999
DOI: 10.1063/1.124020
|View full text |Cite
|
Sign up to set email alerts
|

Continuous refinement of the microstructure during crystallization of supercooled Zr41Ti14Cu12Ni10Be23 melts

Abstract: Isothermal crystallization studies are performed on Zr 41 Ti 14 Cu 12 Ni 10 Be 23 melts between the liquidus and the glass transition temperature. The resulting time-temperature-transformation diagram is in good agreement with the data obtained from containerlessly processed samples. The various solidification products are examined by electron microprobe. The investigations reveal the morphology and typical length scale of the microstructure as well as the primarily solidified phases after crystallizing at dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 15 publications
2
43
0
1
Order By: Relevance
“…It is possible that the incubation time preceding quasicrystal formation at low temperatures is directly influenced by such a process. As it has been suggested in several investigations that decomposition is the rate limiting step for crystallization, 22,23 increases in isothermal stability from Vit1͑-b͒ to Vit4 could therefore be attributed to differences in the timescale for decomposition for each alloy. Löffler et al demonstrated the existence of spatially correlated inhomogeneities in Vit1-Vit4 after annealing at various temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the incubation time preceding quasicrystal formation at low temperatures is directly influenced by such a process. As it has been suggested in several investigations that decomposition is the rate limiting step for crystallization, 22,23 increases in isothermal stability from Vit1͑-b͒ to Vit4 could therefore be attributed to differences in the timescale for decomposition for each alloy. Löffler et al demonstrated the existence of spatially correlated inhomogeneities in Vit1-Vit4 after annealing at various temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…4, where the samples were processed without containers, was obtained from samples crystallized in graphite crucibles. 9 This method is more user friendly compared to ESL and has the advantage of a more reliable temperature reading.…”
Section: ͓S0003-6951͑00͒02231-2͔mentioning
confidence: 99%
“…This is in contrast to Vit1, where at least three different primary solidified phases have been found for the different degrees of undercooling. 9 As such, the crystallization kinetics of PCNP seem to be less complicated than that of Vit1, although x-ray …”
mentioning
confidence: 99%
“…In a complex system like Vit 1 an adequate description of the nucleation process will certainly have to go beyond the concept of steady-state nucleation. 5 Further influences such as, for example, decomposition processes, have to be considered [15][16][17] to explain the fine microstructures of Vit 1. 5 At this point, however, to discuss the different growth kinetics on crystallization the simplified approach of steady-state nucleation serves as a sufficient model.…”
mentioning
confidence: 99%